Potential cardiotoxicity induced by Euodiae Fructus: In vivo and in vitro experiments and untargeted metabolomics research - Dan Zhang; Jintao Lü; Zhixin Ren; Xiaomeng Zhang; Xiaomeng Zhang; Huanzhang Wu; Rina Sa; Rina Sa; Xiaofang Wang; Yu Wang; Yu Wang; Zhijian Lin; et al. (Frontiers Media S.A., 2022)
Background: Euodiae Fructus, a well-known herbal medicine, is widely used in Asia and has also gained in popularity in Western countries over the last decades. It has known side effects, which have been observed in clinical settings, but few studies have reported on its cardiotoxicity.Methods: In the present study, experiments using techniques of untargeted metabolomics clarify the hazardous effects of Euodiae Fructus on cardiac function and metabolism in rats in situations of overdosage and unsuitable syndrome differentiation. In vitro assays are conducted to observe the toxic effects of evodiamine and rutaecarpine, two main chemical constituents of Euodiae Fructus, in H9c2 and neonatal rat cardiomyocytes (NRCMs), with their signaling mechanisms analyzed accordingly.Results: The cardiac cytotoxicity of evodiamine and rutaecarpine in in vivo experiments is associated with remarkable alterations in lactate dehydrogenase, creatine kinase, and mitochondrial membrane potential; also with increased intensity of calcium fluorescence, decreased protein expression of the cGMP-PKG pathway in H9c2 cells, and frequency of spontaneous beat in NRCMs. Additionally, the results in rats with Yin deficiency receiving a high-dosage of Euodiae Fructus suggest obvious cardiac physiological dysfunction, abnormal electrocardiogram, pathological injuries, and decreased expression of PKG protein. At the level of endogenous metabolites, the cardiac side effects of overdose and irrational usage of Euodiae Fructus relate to 34 differential metabolites and 10 metabolic pathways involving among others, the purine metabolism, the glycerophospholipid metabolism, the glycerolipid metabolism, and the sphingolipid metabolism.Conclusion: These findings shed new light on the cardiotoxicity induced by Euodiae Fructus, which might be associated with overdose and unsuitable syndrome differentiation, that comes from modulating the cGMP-PKG pathway and disturbing the metabolic pathways of purine, lipid, and amino acid. Continuing research is needed to ensure pharmacovigilance for the safe administration of Chinese herbs in the future.